Analisis Penentuan Harga Pokok Produksi Dengan Metode Activity Based Costing (Studi Kasus pada PT Beautinesia Media Nusantara) - Salam, Retno Reno Fati; Wijayati, Nureni (Universitas Sam Ratulangi, 2023)
This research is used to examine in depth the application of the ABC system in purchasing HPP PT Beautinesia Media Nusantara products. Data collection techniques consist of observation, documentation, and interviews. The results of the research are 1) Calculation of HPP at PT. Beautynesia Media Nusantara 2020 uses the traditional method of using a single tariff. Comparison of the results of HPP calculations using the traditional method with the ABC method in 2020, namely: (1) Advertorial Service Articles, the traditional HPP method is 1.18% lower than the ABC method; (2) Social Media Management Services, the traditional HPP method is 19.86% lower than the ABC method; (3) KOL Service Management, the traditional HPP method is 2.72% higher than the ABC method; (4) Event Management Services, the traditional HPP method is 51.08% lower than the ABC method; (5) Production Management Services, the traditional HPP method is 21.88% lower than the ABC method; (6) Banner services, the traditional HPP method is 3.59% lower than the ABC method; and (7) Other Services, the traditional HPP method is 2.59% higher than ABC method.